2019
DOI: 10.1002/ppul.24593
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blast lung injury in infant and adult rabbits

Abstract: Background A great number of children suffer from blast lung injury (BLI) worldwide, but there is a little basic study on the topic. Methods Infant (4‐week‐old) and adult New Zealand rabbits were selected. Comparison of BLI characteristics: 16 infant rabbits were randomly divided into a 4.0 MPa group (n = 8, “IRG4.0MPa”) and a 4.5 MPa group (n = 8, “IRG4.5MPa”) and exposed to shock waves of those magnitudes. Eight adult rabbits were exposed to 4.0 MPa (“ARG4.0MPa”). The severity of BLI was compared among these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Unlike previous BLI models that relied on lung ultrasound, blood gas analysis, and imaging for evaluation, monitoring respiratory mechanical changes after BLI through Pes enables more direct and precise quantification of mechanical properties such as airway resistance and lung compliance. The research data can guide clinical practice and provide an experimental foundation ( Li et al, 2020 ; Xue et al, 2020 ; Yang et al, 2020 ; Ding et al, 2022 ). Future research should aim to establish a graded animal model of primary BLI to improve the understanding of the temporal and quantitative relationships between respiratory mechanics and lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous BLI models that relied on lung ultrasound, blood gas analysis, and imaging for evaluation, monitoring respiratory mechanical changes after BLI through Pes enables more direct and precise quantification of mechanical properties such as airway resistance and lung compliance. The research data can guide clinical practice and provide an experimental foundation ( Li et al, 2020 ; Xue et al, 2020 ; Yang et al, 2020 ; Ding et al, 2022 ). Future research should aim to establish a graded animal model of primary BLI to improve the understanding of the temporal and quantitative relationships between respiratory mechanics and lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…The lung wet/dry weight ratio indicated that the moisture content in lung tissue peaked immediately post-injury and then decreased at 24 and 72 h. Accompanied by a rapid increase in average blood pressure post-injury, SpO 2 significantly decreased, recovered to a peak at 24 h, and gradually returned to normal by 72 h, unlike AoY's 6–12 h upto 80% of normal ( 23 ). This suggests that caution should be maintained beyond 24 h post-minor lung injury, with close monitoring up to 72 h. Routine blood examinations showed a rapid increase in WBC and neutrophils, which gradually normalized within 24 h and decreased by 72 h, inconsistent with 12–24 h increasing in Tong C's study ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…These included one healthy control group and four experimental groups each consisting of 10 animals. The study group rabbits were anesthetized by 3% pentobarbital sodium (New Asia Pharmaceutical, Shanghai, China) via ear‐vein injection (1 ml/kg) and subsequently subjected to aright chest puncture using a Hopkinson Bar with an acceleration of 2,600 g. Rabbits in the study groups were subjected to surgery and cholecystectomy following puncture, either immediately (0 hr), or kept for 24, 48, or 72 hr before cholecystectomy (Chen et al, 2020; Yang et al, 2020). Hematoxylin‐eosin staining was used to examine rabbit lung injury.…”
Section: Methodsmentioning
confidence: 99%